Factors Associated with Teenage Pregnancy: A Hospital-Based Case-Control Study - Chet Kant Bhusal (Journal of Karnali Academy of Health Sciences)
Background: Teenage pregnancy is a major public health problem and is considered to be high risk for maternal health, pregnancy outcomes, and long-term effects. This study aims to determine the factors associated with teenage pregnancy among pregnant teenagers and non-teenagers in a tertiary hospital of Nepal.